INFORMATION AND COMMUNICATION SUPPORT OF QUALITY MANAGEMENT DECISIONS - M. Borovyk; M. Novikova; О. Козирєва; O. Krasnonosova; M. Volkova (Фінансово-кредитна діяльність: проблеми теорії та практики, 2021)
Abstract. The article examines the impact of information and communication support on the process of making quality management decisions aimed at achieving sustainable development of higher education institutions in the context of Ukraine’s integration into the European educational space. The essence of sustainable development of higher education institutions and the specifics of its achievement within competition of educational services in the market, which is especially acute in the conditions of European integration, are considered. The necessity of using effective information and communication support in the development of high-quality management decisions aimed at achieving sustainable development of higher education institutions is determined. The process of making managerial decisions is considered and the quality of making managerial decisions is characterized. The organizational aspects of making quality management decisions are determined. The sequence of actions on the decision of the problems arising in the course of activities of the higher education institutions is offered. The approaches to be considered in the course of accepting qualitative administrative decisions directed on the achievement of sustainable development of higher education institutions on the basis of management of information and communication maintenance of their activity are considered. The influence of people who make management decisions on their quality and effectiveness is determined. The requirements to the quality criteria of managerial decision-making, which are put forward in the development of economic and mathematical models of managerial decision-making aimed at achieving sustainable development of higher education institutions, are studied. The principles of optimization of management decisions are considered.